Does Too Much Energy Consumption Harm Economic Growth for Turkish Republics in The Transition Process? New Evidence on Threshold Effects - Aydın, Celil; Esen, Ömer (International Journal of Energy Economics and Policy, 2017)
This paper examines whether the effect of energy consumption on economic growth is dependent on the level of energy intensity for 5 Turkish republics in the transition process over the period 1991–2012. These economies are divided into two groups in the context of their energy balance. The first group comprises all of the Turkish republics in the transition process while the second group is composed of only the net energy exporter countries among them. Using an innovative dynamic panel threshold technique, the estimated threshold of the energy intensity for the first group is 0.68 per cent, while for the second group countries the threshold is 0.44 per cent. The empirical results indicate that the energy consumption rate above the threshold energy intensity level adversely affects the economic growth, but this negative relationship becomes positive one when the energy consumption is below the threshold level. These findings reveal that the energy consumption is beneficial to economic growth only up to a certain threshold of the energy intensity; beyond the threshold level further the consumption tends to adversely affect the growth. In this regard, policy makers in the transition economies should not ignore threshold levels within the context of energy intensity while determining energy policies. Keywords: Dynamic Panel Threshold Analysis, Energy Consumption, Economic Growth, Energy Intensity JEL Classifications: C24, Q43, O11